Absenteeism: a study of its factor and prevention among the form four & five at secondary school students in SM St Peter Telipok Kota Kinabalu / Azidah Abdul Aziz - Abdul Aziz, Azidah (2007)
The purpose of this study is seeing the factors of absenteeism and its prevention among form four and five at SM ST Peter Telipok Kota Kinabalu. There are 152 respondents participated in the survey. The research objectives are to study the factor of absenteeism, to study the correlation of the factors with school absenteeism and to what extent of this factor, to study the prevention of absenteeism through school enforcement to prevent absenteeism, and To make recommendation on how to prevent the absenteeism. However. I had found the there is no significant between the variable ob absenteeism. As a result, I had a recommended more preventions action to prevent absenteeism behavior.